PENERAPAN SUPERVISI PENDIDIKAN DALAM MENINGKATKAN PROFESIONALISME GURU DI MI AL-AMIEN PRENDUAN 2022/2023 - Achmad Maulidi; Madona Agustin Sari (Dewantara : Jurnal Pendidikan Sosial Humaniora, 2023)
Supervision is an assessment process or procedure in giving directions and conducting critical assessments of the learning process. Supervision is an activity carried out by the principal to supervise and direct all educational devices in order to achieve educational goals. The principal as a supervisor who carries out the supervision program starts with planning, implementation and follow-up. This study aims, (1) how is the application of educational supervision in increasing the professionalism of MI Al-Amien teachers, (2) what are the inhibiting and supporting factors in the application of educational supervision in increasing the professionalism of MI Al-Amien teachers This study used a descriptive qualitative approach where the research went directly to the field, while the data collection techniques in this study varied with interview, observation and documentation methods, data collection using structured interview methods. The research findings show that: 1) the application of educational supervision in improving teacher professionalism, namely: a) the principal is active in checking the lesson plan every week and actively making prota and promissory notes; b) the school principal actively conducts class visits, with; c) the school principal is active in supervising education at the beginning of every month by evaluating the teacher; d) the school principal always takes part in PKKM activities which are held every year; i) 80% of teachers are in linear institutions. 2) the implementation of educational supervision can be said to be effective in increasing teacher professionalism because teacher professionalism is getting better and orderly starting from planning, carrying out learning to evaluating/assessing learning.